Influence of Leadership Style, Competence, and Motivation on Employee Performance through Job Satisfaction at AUR Beduri Health Center Jambi - Rika Rohim; Yulasmi Yulasmi; Zefriyenni Zefriyenni (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of leadership style, competence, and motivation on employee performance with job satisfaction as an intervening variable at the Aur Beduri Community Health Center, Nalo Tantan District, Merangin Regency, Jambi. The study uses a quantitative approach with Partial Least Square (PLS) analysis through the SmartPLS application. The object of this study is the employees of the Aur Beduri Community Health Center, Nalo Tantan District, Marangin Regency, Jambi, Indonesia. This study uses a descriptive and causal research design. The population in this study is 64 employees of the Aur Beduri Community Health Center. In this study, the sample was taken with a saturated sample design, namely the entire population being sampled, so the sample in this study was 64 people. Based on the literature review and hypothesis formulation, the variables in this study are independent, dependent, and intervening variables. Independent variables include Leadership Style, Competence, Motivation. The intervening variable in this study is Job Satisfaction. The dependent variable is also called the bound variable, namely the value of which is influenced by the independent variable, which is the dependent variable in this study is Job Satisfaction (Y). The results of the study showed that leadership style, competence, and motivation had a positive and significant effect on job satisfaction. Furthermore, job satisfaction had a positive and significant effect on employee performance. Competence and motivation were shown to have a positive and significant effect on employee performance, while leadership style did not have a significant direct effect on performance. However, job satisfaction was shown to mediate the influence of leadership style, competence, and motivation on employee performance. This finding indicates that improving leadership quality, competence, and motivation can increase job satisfaction, which in turn contributes to improved employee performance. This study provides practical implications for Community Health Center management to strengthen participatory leadership styles, improve employee competence through training, and develop appropriate motivation systems to improve the performance of health workers.